A kötelékvédő szerepének változásai az egyházjogban, kitekintéssel a magyar világi perjogra - Tamási, Anna Éva (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
The defender of the bond is one of the most important officials at the ecclesiastical courts. In this paper I examine the changes of this office both in canonical legislation and in jurisdictional practise (and in Hungarian private law). I present the practise of the holy see of Veszprém and Székesfehérvár in matrimonial cases in the 19th and 20th century.